The role of police in assemblies: ethical implications, imperatives, and interventions - Schiewek, Werner (Public Order Policing, 2024)
This chapter highlights the importance of assemblies for a thriving democracy. As a democratic virtue, assemblies should not be prevented but in fact facilitated. However, assemblies are associated with individual, social, and moral risks for all participants. To help mitigate risks associated with assemblies, the moral expectations of police, including internal and external expectations, and the tensions between them are analyzed. Awareness of these challenges can help police better prepare their organizations and officers. Suggestions for personal and organizational planning are grounded in different ethical approaches and the four classical cardinal virtues.